2015
DOI: 10.1002/anie.201502241
|View full text |Cite
|
Sign up to set email alerts
|

Ordering of PCDTBT Revealed by Time‐Resolved Electron Paramagnetic Resonance Spectroscopy of Its Triplet Excitons

Abstract: Time-resolved electron paramagnetic resonance (TREPR) spectroscopy is shown to be a powerful tool to characterize triplet excitons of conjugated polymers. The resulting spectra are highly sensitive to the orientation of the molecule. In thin films cast on PET film, the molecules' orientation with respect to the surface plane can be determined, providing access to sample morphology on a microscopic scale. Surprisingly, the conjugated polymer investigated here, a promising material for organic photovoltaics, exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 30 publications
2
73
0
1
Order By: Relevance
“…[20] Our assignment of the unusually large line widths observed in the TREPR data to a high intrinsic flexibility of PNDIT2 and its building blocks retained even in the polymer if dissolved in 1-chloronaphthalene is consistent with prior results. All other molecules investigated here show much smaller line widths, although still pretty large as compared with other conjugated polymers such as poly(3-hexylthiophene) (P3HT) or poly[N-9′-heptadecanyl-2,7-carbazole-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole)] (PCDTBT).…”
Section: Large Conformational Flexibility Even For a Conjugated Polymersupporting
confidence: 89%
See 2 more Smart Citations
“…[20] Our assignment of the unusually large line widths observed in the TREPR data to a high intrinsic flexibility of PNDIT2 and its building blocks retained even in the polymer if dissolved in 1-chloronaphthalene is consistent with prior results. All other molecules investigated here show much smaller line widths, although still pretty large as compared with other conjugated polymers such as poly(3-hexylthiophene) (P3HT) or poly[N-9′-heptadecanyl-2,7-carbazole-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole)] (PCDTBT).…”
Section: Large Conformational Flexibility Even For a Conjugated Polymersupporting
confidence: 89%
“…[20,21] Optical excitation at the respective wavelengths in the visible range was carried out using an optical parametric oscillator (OPO) pumped by an Nd:YAG laser. [20,21] Optical excitation at the respective wavelengths in the visible range was carried out using an optical parametric oscillator (OPO) pumped by an Nd:YAG laser.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that films of the polymer PCDTBT fabricated using similar methods to those employed here exhibited partial orientation effects in the triplet exciton TR-EPR spectrum. 72 …”
Section: Resultsmentioning
confidence: 99%
“…18,19 The low-bandgap and thermally stable copolymer poly[N-9′-heptadecanyl-2,7-carbazole-alt- 21 Also beneficial for charge injection is a face on orientation of the PCDTBT backbone in as-cast films. 22 Due to the low-lying HOMO level of 5.5 eV, PCDTBT exhibits ambipolar character and can also be used as acceptor material in combination with strong donors such as P3HT. 23 Recently, we have shown that PCDTBT is prone to carbazole (Cbz) homocoupling defects which add to the two most important parameters molecular weight and dispersity.…”
Section: Introductionmentioning
confidence: 99%